2018
DOI: 10.1016/s2214-109x(18)30386-3
|View full text |Cite|
|
Sign up to set email alerts
|

High-quality health systems in the Sustainable Development Goals era: time for a revolution

Abstract: The Lancet Global Health Commission and respecting all workers to deliver the best care possible. Fourth, governments and civil society should ignite demand for quality in the population to empower people to hold systems accountable and actively seek high-quality care. Additional targeted actions in areas such as health financing, management, district-level learning, and others can complement these efforts. What works in one setting might not work elsewhere, and improvement efforts should be adapted for local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
2,594
2
54

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,410 publications
(2,689 citation statements)
references
References 243 publications
(363 reference statements)
39
2,594
2
54
Order By: Relevance
“…When governments do seek to improve health worker performance, efforts focus on in‐service training for clinicians already in practice. Studies have found that such training has only a modest impact on quality and cannot by itself close the large quality deficits observed .…”
Section: Introductionmentioning
confidence: 98%
“…When governments do seek to improve health worker performance, efforts focus on in‐service training for clinicians already in practice. Studies have found that such training has only a modest impact on quality and cannot by itself close the large quality deficits observed .…”
Section: Introductionmentioning
confidence: 98%
“…There is a long road ahead toward the equitable implementation of quality care, 30 meeting the health-related United Nations Sustainable Development Goals 31 and universal health coverage. Science shows us that the journey would be considerably shortened through the implementation of midwifery that meets the international standards set by the International Confederation of Midwives.…”
Section: Moving Forward-global Actionmentioning
confidence: 99%
“…Delivery of high quality and evidence‐based health care is a major imperative worldwide. Although major strides have been made in most countries with regard to developing high‐quality health services towards better patient outcomes over the past two decades, major variations in health‐care delivery still exist and this is quite pervasive in most health‐care facilities in low‐/middle‐income countries (LMICs), where substandard care is provided to patients culminating in poor patient outcomes . For example, it is estimated that up to 8.4 million deaths are recorded annually in LMICs as a result of compromised quality of care .…”
Section: Introductionmentioning
confidence: 99%